Learning Mechanism Practices for Learners’ Academic Achievement in Schools for Special Children of Assam - Alom, Jahangir Hussain (International Journal of Psychosocial Rehabilitation, 2020)
Learning mechanisms plays crucial role in the process of education. Education for children with special needs is an emerging trend worldwide, and many countries have established monitoring activities and mechanisms of education for special needs children at institutional, local and national level. The paper intends to study the effect of special learning mechanisms on learners’ academic achievement, and qualification and training level of the teachers of special schools of Assam. Random sampling technique was applied for selecting the sample, and descriptive survey method was applied to collect data. Both qualitative and quantitative data analysis techniques were used. The major inferences of the study have been revealed that the different categories of special needs children are taught through various mechanisms such as- visual impaired students were taught through Braille method, flash chart; hearing impaired students were taught through sign language and hearing devices; mentally challenged students were provided with the basic 3Rs and life skill training. The effect of the special learning mechanisms reflected remarkable academic achievements of the students, for instance, the students of Sudhir Ch. Chakravorty Academy for blind obtained 92% average marks in the final examination of 2009-10 session. The paper also showed that the teachers working in the schools for special children of Assam are found to be highly experienced (i.e., 56.67% up to 10 years, 25.23% up to 20 years and 17.78% above 20 years) and trained (85.56% trained and 14.44% untrained) teachers.